Цианобактерия Synechococcus cedrorum — тест-культура для биоиндикации токсичности новых химически синтезированных лекарственных веществ - Жолобак, Н.М.; Лысенко, Т.Г. (Видавничий дім "Академперіодика" НАН України, 2009)
Обгрунтовано використання цiанобактерiй як тест-об’єктiв для скринiнгу нових лiкарських противiрусних препаратiв. Показано чiтку кореляцiю токсичностi дослiджених сполук для культури Synechococcus cedrorum i контрольної тест-культури, що стандартно використовується для вивчення властивостей новосинтезованих сполук. Запропонована тест-система цiанобактерiя S. cedrorum — нова, екологiчно безпечна, оперативна, технологiчна, а також адекватна iншим сучасним методам дiагностики. The work is devoted to the substantiation of the use of cyanobacteria as a test-object for the screening of new antiviral medicinal substances. Clear correlation of experimental substances’ toxicity between culture of S. cedrorum and control test-cultures which are usually used in the investigation of new synthesized substances’ properties is shown. The proposed test-system of cyanobacteria S. cedrorum is new, environmentally safe, operational, technological, and adequate to other diagnostic methods used in current medicine and veterinary practice.